2006
DOI: 10.1074/jbc.c600038200
|View full text |Cite
|
Sign up to set email alerts
|

hSnm1B Is a Novel Telomere-associated Protein

Abstract: Artemis, a member of the ␤-CASP family, has been implicated in the regulation of both telomere stability and length. Prompted by this, we examined whether the other two putative DNA-binding members of this family, hSnm1A and hSnm1B, may associate with telomeres. hSnm1A was found to not interact with the telomere. Conversely, hSnm1B was found to associate with telomeres in vivo by both immunofluorescence and chromatin immunoprecipitation. Furthermore, the C terminus of hSnm1B was shown to interact with the TRF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 34 publications
3
57
0
Order By: Relevance
“…Further IF studies revealed that the majority of hSNM1B-foci co-localized with the telomere core protein, TRF1, and are therefore localized at telomeres. These findings substantiate previous reports on the localization of ectopic expressed hSNM1B at telomeres [12,14,16]. The observation that only a fraction of cells contained hSNM1B foci suggests a transient, cell cycle dependent function for hSNM1B at telomeres consistent with reports that hSNM1B functions in repressing the "DNA-damage" signal at telomeres during or after their replication [13].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Further IF studies revealed that the majority of hSNM1B-foci co-localized with the telomere core protein, TRF1, and are therefore localized at telomeres. These findings substantiate previous reports on the localization of ectopic expressed hSNM1B at telomeres [12,14,16]. The observation that only a fraction of cells contained hSNM1B foci suggests a transient, cell cycle dependent function for hSNM1B at telomeres consistent with reports that hSNM1B functions in repressing the "DNA-damage" signal at telomeres during or after their replication [13].…”
Section: Discussionsupporting
confidence: 81%
“…As shown above, the anti-hSNM1B antibodies were able to detect hSNM1B in IF experiments which allowed us to determine whether endogenous hSNM1B localizes to telomeres, as suggested by the yeast-two-hybrid and co-IP results and previously published results on ectopic overexpressed hSNM1B [12][13][14][15]. Double staining of hSNM1B and either of the telomere markers, TRF1 or TRF2, demonstrated a high degree of co-localization of these proteins ( Figure 2C) and showing, for the first time, that the majority of endogenous hSNM1B foci are localized at telomers.…”
Section: Interaction Between Trf2 and Hsnm1bmentioning
confidence: 81%
See 1 more Smart Citation
“…Together our findings demonstrate that Snm1B is specifically involved in mediating resistance to ICLinducing compounds by its role in promoting replication fork collapse, which leads to activation of ATMmediated cell cycle arrest and likely initiation of removal of the lesion. As Snm1B/Apollo has also been implicated in telomere protection during S phase (Freibaum and Counter, 2006;Lenain et al, 2006;van Overbeek and de Lange, 2006), it is clear that it has a multifunctional role in maintenance of genomic stability, and experiments designed to assess its role as a tumor suppressor merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In human cells siRNA-mediated knockdown of SNM1B has been shown to result in moderate hypersensitivity to cisplatin, MMC and IR (Demuth et al, 2004). Also, several recent papers have demonstrated a novel function for Snm1B/Apollo namely that it interacts with the telomere protein TRF2 and protects telomeres from the DNA repair machinery during S phase (Freibaum and Counter, 2006;Lenain et al, 2006;van Overbeek and de Lange, 2006).…”
Section: Introductionmentioning
confidence: 99%